Analisis Kebutuhan Media Aplikasi Android Berbasis Kearifan Lokal Gusjigang untuk Pembelajaran Kaidah Kebahasaan Siswa SD - Muhammad Afdholil Kholiqoh Insani; Muhammad Zakky Ali; Sigit Ariyanto; Rani Setiawaty (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to analyze the needs for an Android-based learning media integrated with Gusjigang local wisdom in teaching Indonesian language rules to second-grade elementary school students. The research employed a descriptive qualitative approach involving teachers and 19 students of SD 1 Panjang, Kudus Regency. Data were collected through classroom observations, questionnaires, and semi-structured interviews. The findings indicate that although most students understand the teacher’s explanation of language rules, the use of interactive digital media in learning remains limited. Students showed a strong preference for engaging learning media, interactive exercises, and visually supported materials, while their familiarity with Gusjigang values was relatively low. However, a significant number of students expressed interest in learning Indonesian through culturally based Android applications. These results highlight the need for developing Android-based learning media that integrates visual, audio, interactive quizzes, and local cultural values to enhance students’ motivation, understanding, and engagement in learning Indonesian language rules. Integrating Gusjigang local wisdom is expected to support both academic achievement and character development in elementary education.